2002
DOI: 10.1002/1522-2683(200206)23:11<1618::aid-elps1618>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of class I and II organic modifiers on retention and selectivity in vesicle electrokinetic chromatography

Abstract: Vesicles are large aggregates of surfactant monomers consisting of a spherical bilayer surrounding an internal cavity of solvent. The bilayer structure allows vesicles to be attractive models for the study of various transmembrane and binding processes. The use of thermodynamically stable vesicles (TSV) formed from oppositely charged surfactants for use as a pseudostationary phase in electrokinetic chromatography (EKC) was first accomplished using dodecyltrimethylammonium bromide and sodium dodecyl sulfate (DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Interestingly, the three positional isomers were eluted in the same order (o < p < m) using the two catanionic vesicle systems and two micelle systems, respectively. It was previously reported that p-nitrotoluene was eluted ahead of o-nitrotoluene using series of catanionic surfactant vesicles including DTAB/SDS, CTAB/SOS, OTAB/SDS and C 8 NE 3 Br/SDBS, while o-nitrotoluene was eluted first followed by p-nitrotoluene using the SDS micelles [2,5,7,10,33]. Clearly, the elution order of p-and o-nitrotoluene, obtained using the HFIP-modified and TFE-modified CTAB/SDS vesicles in our present study, was in contrast to that using the catanionic surfactant vesicles described in the above literatures.…”
Section: Separation Of Nitrotoluene Positional Isomersmentioning
confidence: 97%
See 3 more Smart Citations
“…Interestingly, the three positional isomers were eluted in the same order (o < p < m) using the two catanionic vesicle systems and two micelle systems, respectively. It was previously reported that p-nitrotoluene was eluted ahead of o-nitrotoluene using series of catanionic surfactant vesicles including DTAB/SDS, CTAB/SOS, OTAB/SDS and C 8 NE 3 Br/SDBS, while o-nitrotoluene was eluted first followed by p-nitrotoluene using the SDS micelles [2,5,7,10,33]. Clearly, the elution order of p-and o-nitrotoluene, obtained using the HFIP-modified and TFE-modified CTAB/SDS vesicles in our present study, was in contrast to that using the catanionic surfactant vesicles described in the above literatures.…”
Section: Separation Of Nitrotoluene Positional Isomersmentioning
confidence: 97%
“…It has been reported that the addition of organic modifiers to a catanionic surfactant vesicles system can exert a significant influence on the electrophoretic parameters of the system [7,8]. In this study, the effect of HFIP on the electrophoretic parameters of a CTAB/SDS vesicle system was investigated in detail and the results are shown in Table 1.…”
Section: Electrophoretic Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…It was referred to as solvent modified micelle, or swollen micelle. Recently, 1-butanol modified MEKC was proven to be similar to MEEKC in performance with respect to both separation selectivity and separation efficiency [15][16][17][18][19][20][21]. Wen [22] had compared MEEKC with solvent modified MEKC on rapid separation of heroin, amphetamine and their basic impurities.…”
Section: Introductionmentioning
confidence: 99%